2002
DOI: 10.1183/09031936.02.00293702
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide but not carbon monoxide is continuously released in the human nasal airways

Abstract: Results from different laboratories indicate that nitric oxide (NO) and carbon monoxide (CO) coexist in the human airways both in health and disease. These gases are present in exhaled human breath and high concentrations of NO as well as CO have been reported in the nasal airways. In addition, exhaled CO and NO are increased in patients with airways inflammation. NO and CO were measured simultaneously in orally exhaled air and in air sampled from the nose in 18 healthy subjects using chemiluminescence (for NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…No evidence of CO release in the nasal airways was found. In fact, the authors described an absorption of CO when low levels of this gas were flushed through the nasal cavity and reported that nasal CO also remained undetectable after smoking (28). Moreover, recently it was shown that orally exhaled CO is not flow-dependent, whereas NO is (29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…No evidence of CO release in the nasal airways was found. In fact, the authors described an absorption of CO when low levels of this gas were flushed through the nasal cavity and reported that nasal CO also remained undetectable after smoking (28). Moreover, recently it was shown that orally exhaled CO is not flow-dependent, whereas NO is (29).…”
Section: Discussionmentioning
confidence: 97%
“…It had been suggested that CO was also released in the nose and paranasal sinuses (27). However, a recent study analyzed NO and CO simultaneously in nasal air as well as in orally exhaled air by collecting the airway samples in bags (28). No evidence of CO release in the nasal airways was found.…”
Section: Discussionmentioning
confidence: 97%
“…NO findet sich auch im Exhalat, insbesondere aus der Nase (dabei werden bei Gesunden Konzentrationen bis zu 650 μg/ m³ erreicht [93]. NO oxidiert an der Luft rasch zu NO 2 , das deutlich besser wasserlöslich ist [91].…”
Section: Stickoxideunclassified
“…In adults, NO is produced by the paranasal sinuses and its exhaled concentrations elevate in normal subjects after digested, intravenous, or inhaled L-arginine [51]. In normal subjects, nasal air contains only NO, whereas orally exhaled air contains both NO and CO [52]. A study demonstrated that 2-pentylfuran may be an exhaled biomarker for detection of pulmonary fungal and Streptococcus pneumoniae infections [53].…”
Section: Exhaled Markers In Respiratory Infectionsmentioning
confidence: 99%